Effects of COVID-19 on Geographical Trends in the Orthopaedic Surgery Residency Match. Issue 3 (21st July 2022) - Holderread, Brendan M.; Han, Alex; Mand, Davinder S.; Liu, Jonathan; Harris, Joshua D.; Liberman, Shari R.
Abstract : BACKGROUND: Historically, medical students often match within the same geographic location or to an orthopaedic surgery residency program affiliated with their medical school. The objective of this investigation was to determine differences in geographic trends between orthopaedic residents matching before and during the Coronavirus-19 (COVID-19) pandemic. METHODS: This study analyzed 2 groups of orthopaedic residents: Pre-COVID cohort (years 2016-2020) and COVID-impacted cohort (year 2021). A list of accredited orthopaedic surgery residency programs (n = 202) was obtained. Orthopaedic residency program webpages were located (region [n = 4], division [n = 9], state [n = 50]). For each resident, their medical school and year of postgraduate training were recorded. Year 2021 resident information was obtained from the orthopaedic residency program webpages, social media accounts, and medical school match lists. Residency programs affiliated with a medical school were also assigned. Descriptive statistics were performed. Two sample Student t tests with Bonferroni correction applied to p-values (α < 0.05 significant) were performed. RESULTS: There were 4, 832 residents analyzed (4, 074 in Pre-COVID cohort; 758 in COVID-impacted cohort [758/868 of all positions in 2021 Match]). Statistically significant differences were detected between the COVID-impacted cohort (39.6%, p < 0.001) matching in the same state as their medical school (Pre-COVID 33.1%) and the COVID-impacted cohort (28.0%, p < 0.001) matching to a residency program affiliated with their medical school (Pre-COVID 21.2%). In the COVID-impacted cohort, students who matched in state matched to their home program more frequently (69.3%) compared with the Pre-COVID cohort (60.5%). Geographically, there was a difference in the COVID-impacted cohort (52.5%, p < 0.011) matching in the same division (Pre-COVID 47.5%). No statistically significant differences were identified for residents matching to the same region as their medical school (Pre-COVID 60.1%; COVID-impacted 61%, p = 0.968). CONCLUSION: Residents matching in the same state, in the same division, and to a residency program affiliated with their medical school increased significantly in the COVID-impacted cohort. There was no difference between cohorts matching in the same region as their medical school. Level of Evidence: Observational/Cross-Sectional